Association of maternal socio-biological factors with birth-weight of newborn baby (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: socio-biological factors; parity; pregnancy duration; spacing; association; birth weightdoi: 10.3329/jcmcta.v19i1.3851Journal of Chittagong Medical College Teachers' Association 2008: 19(1):37-42